ANALYSIS OF E-COMMERCE CONSUMER SATISFACTION LEVEL WITH THE TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH - Kurniawan, Dendy; Maulana, Putri Anindya; Zusrony, Edwin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The presence of online shopping or e-commerce applications in Indonesia in the era of the covid-19 pandemic is very helpful to meet all needs and avoid crowds and direct contact. The increase in the number of e-commerce users can be seen from the level of visits to e-commerce applications which is almost close to the total population of Indonesia of 270 million visits. This research was conducted on 100 respondents consisting of XYZ University students in the city of Semarang to measure the level of satisfaction in the use of e-commerce with the Technology Acceptance Model approach. Using a Likert scale with an indicator rating of 1-5, the researcher wants to know student satisfaction in the use of e-commerce in everyday life. The result is the majority of students answered strongly agree on average about 70%.